Siponimod: Disentangling disability and relapses in secondary progressive multiple sclerosis - Cree, Bruce Ac; Magnusson, Baldur; Rouyrre, Nicolas; Fox, Robert J; Giovannoni, Gavin; Vermersch, Patrick; Bar-Or, Amit; Gold, Ralf; Piani Meier, Daniela; Karlsson, Göril; Tomic, Davorka; Wolf, Christian; et al. (Multiple sclerosis, 2021)
In multiple sclerosis, impact of treatment on disability progression can be confounded if treatment also reduces relapses. To distinguish siponimod's direct effects on disability progression from those on relapses in the EXPAND phase 3 trial. Three estimands, one based on principal stratum and two on hypothetical scenarios (no relapses, or equal relapses in both treatment arms), were defined to determine the extent to which siponimod's effects on 3- and 6-month confirmed disability progression were independent of on-study relapses. Principal stratum analysis estimated that siponimod reduced the risk of 3- and 6-month confirmed disability progression by 14%-20% and 29%-33%, respectively, compared with placebo in non-relapsing patients. In the hypothetical scenarios, risk reductions independent of relapses were 14%-18% and 23% for 3- and 6-month confirmed disability progression, respectively. By controlling the confounding impact of on-study relapses on confirmed disability progression, these statistical approaches provide a methodological framework to assess treatment effects on disability progression in relapsing and non-relapsing patients. The analyses support that siponimod may be useful for treating secondary progressive multiple sclerosis in patients with or without relapses.